PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT KUNJUNGAN WISATAWAN DI PANTAI AROFAN DESA TIGARAS KABUPATEN SIMALUNGUN - Yesa April Siahaan; Anggun Tiur Ida Sinaga; Injen Pardamean Butarbutar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The study aims to determine The Efect of Promotion And Service Quality On Arofan Beach Tourist Interest In Tigaras Village. This research uses quantitative research and survey methods. The population in this study were visitors to arofan beach in Tigaras village with a sample size of 100 respondents obtained based on Non Probability sampling with technique Accidential Sampling. Data collection techniques using observation, questionnaires and documentation. The research quesitionnaire as tasted using validity and reability tests. The data analysis technique used is the classical assumption test and hypothesis testing.The results of this study indicate that there is a positive influence between promotion and interest in tourist visits, there is a positive effect of service quality on visiting interest, there is an influence of promotion and service quality on visiting interest